2002
DOI: 10.1046/j.1464-410x.2002.02641.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of 18fluoro‐2‐deoxyglucose positron emission tomography in initial staging and re‐staging after chemotherapy for testicular germ cell tumours

Abstract: Objective To investigate the role of 18 fluoro-2-deoxyglucose positron emission tomography (FDG-PET) tumorous residual mass the FDG-PET scan was clearly positive; in four of 12 with mature teratoma and inflammation components retroperitoneally, the FDG-PET was also positive. In contrast, eight patients with solitary mature teratoma had a negative PET result. In four of five patients with necrosis after chemotherapy the PET result was correctly negative. All eight patients on surveillance had a negative PET s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(55 citation statements)
references
References 26 publications
2
50
0
3
Order By: Relevance
“…A postchemotherapy residual mass is the most common indication for FDG-PET [Karapetis et al 2003]. In NSGCTs, PET scans cannot differentiate teratoma from necrosis/fibrosis, but has been used to predict fibrotic residual mass in patients with no teratoma in their primary tumor [Spermon et al 2002]. Although a positive PET scan is highly suggestive of residual viable cancer, false-negative rates of up to 40% have been reported in a prospective trial [Pfannenberg et al 2004].…”
Section: Imaging Studiesmentioning
confidence: 99%
“…A postchemotherapy residual mass is the most common indication for FDG-PET [Karapetis et al 2003]. In NSGCTs, PET scans cannot differentiate teratoma from necrosis/fibrosis, but has been used to predict fibrotic residual mass in patients with no teratoma in their primary tumor [Spermon et al 2002]. Although a positive PET scan is highly suggestive of residual viable cancer, false-negative rates of up to 40% have been reported in a prospective trial [Pfannenberg et al 2004].…”
Section: Imaging Studiesmentioning
confidence: 99%
“…False-negative and the unsatisfactory sensitivity may be given in following conditions. Micro-tumor and micrometastases have lower uptake values which might be masked by the higher uptake of the primary tumor, which can infect the false-negative results (Hoekstra et al, 1993;Cremerius et al, 1998;Hofer et al, 2001;Spermon et al, 2002;Antoch et al, 2004). In addition, timing of the PET scan is important, for patients examined within 10-14 days of chemotherapy may result in false-negative (Cremerius et al, 1998, Hain, 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 21 studies were excluded for undesirable article types (n=21), not written in English (n=6), and insufficient data (n=4), letter (n=2), case report (n=1), and review (n=8). Thus, 16 studies were included in our final dataset for the meta-analysis (Cremerius et al, 1998;Albers et al, 1999;Cremerius et al, 1999;Hain et al, 2000;Bokemeyer et al, 2002;Spermon et al, 2002;Tsatalpas et al, 2002;Lassen et al, 2003;De Santis et al, 2004;Becherer et al, 2005;de Wit et al, 2008;Hinz et al, 2008;Oechsle et al, 2008;Akbulut et al, 2011;Bachner et al, 2012;Siekiera et al, 2012). The flowchart of study selection was shown in Figure 1.…”
Section: Study Selection and Characteristics Of Studies In Our Analysismentioning
confidence: 99%
“…Matür teratomun F-18 FDG ile görüntülenmesi normal/normale yakın glikoz metabolizması olan, düşük proliferasyon oranı gösteren benign bir oluşum olduğundan zordur (41,42,43,44). Tedavi genel olarak total cerrahi yapılmasıdır.…”
Section: Germ Hücreli Tümörlerunclassified